Trap Location and Premises Condition Influences on Aedes aegypti (Diptera: Culicidae) Catches Using Biogents Sentinel Traps During a 'Rear and Release' Program: Implications for Designing Surveillance Programs. Issue 4 (28th February 2019) - Staunton, Kyran M; Yeeles, Peter; Townsend, Michael; Nowrouzi, Somayeh; Paton, Christopher J; Trewin, Brendan; Pagendam, Daniel; Bondarenco, Artiom; Devine, Gregor J; Snoad, Nigel; Beebe, Nigel W; Ritchie, Scott A
Abstract: As the incidence of arboviral diseases such as dengue, Zika, chikungunya, and yellow fever increases globally, controlling their primary vector, Aedes aegypti (L.) (Diptera: Culicidae), is of greater importance than ever before. Mosquito control programs rely heavily on effective adult surveillance to ensure methodological efficacy. The Biogents Sentinel (BGS) trap is the gold standard for surveilling adult Aedes mosquitoes and is commonly deployed worldwide, including during modern 'rear and release' programs. Despite its extensive use, few studies have directly assessed environmental characteristics that affect BGS trap catches, let alone how these influences change during 'rear and release' programs. We assessed male and female Ae. aegypti spatial stability, as well as premises condition and trap location influences on BGS trap catches, as part of Debug Innisfail 'rear and release' program in northern Australia. We found similar trends in spatial stability of male and female mosquitoes at both weekly and monthly resolutions. From surveillance in locations where no males were released, reduced catches were found at premises that contained somewhat damaged houses and unscreened properties. In addition, when traps were located in areas that were unsheltered, more than 10 m from commonly used sitting areas or more visually complex catches were also negatively affected. In locations where males were released, we found that traps in treatment sites, relative to control sites, displayed increased catches in heavily shaded premises and were inconsistently influenced by differences in house sets and building materials. Such findings have valuable implications for a range of Ae. aegypti surveillance programs.